Fascinating klong-toey: The study of slum tourism development - JARUWAN KUMPETCH; PIMNARA KUMPETCH; PASIT KUMPETCH (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The primary goal is to find the most effective strategies for boosting tourism in Klong-Toey District, Thailand’s first slum. As part of the investigation into urban equality, researchers are looking into the potential for tourism development in Klong-Toey.Method: In-depth interviews with community leaders and agents involved in slum tourism development, as well as Participant Observation in the communication process, are used as research methods.Findings: The study shows that the number of people working in Thailand’s agricultural sector is affected by urbanization. Bangkok had seen an influx of people from all over Thailand since 1938, when work began at the Port Authority of Thailand, drawing them in search of employment opportunities in the city’s infrastructure development and construction industries. A country can increase its GDP relatively quickly and easily by investing in and promoting its tourism industry. Health tourism, agricultural tourism, and tourism to officially recognized historic sites are just a few examples of subsets within the broader tourism industry.Implications/Novel Contribution: The findings of this investigation can be used to shape more effective tourism policies.